O05-2 Increased severity of radiologic pneumoconiosis among former us coal miners; federal black lung program data 2001 to 2013. (1st September 2016) - Graber, Judith; Harris, Gerald; Almberg, Kirsten; Petsonk, E Lee; Rose, Cecile; Cohen, Robert
Abstract : Background: In 1970, the US mandated airborne dust exposure limits in mines and established the Federal Black Lung Program (FBLP). Coal miners who apply for FBLP benefits undergo diagnostic testing including chest x-ray and spirometry. We hypothesised that claimants who worked only after 1970 would have lower rates of more advanced coalmine dust lung disease. Methods: We analysed de-identified data from miners' last FBLP claim filed between 2001 and 2013. Among 24, 802 total claims, we assessed the prevalence of: (1) ILO profusion categories (simple coal workers' pneumoconiosis [CWP] = 1/0 [n = 4, 578]; 1/1–1/2 [n = 3, 803]); advanced CWP (2/1–3/+ [n = 1, 116]); or progressive massive fibrosis (PMF =A, B, or C [n = 986]); and (2) ATS classification of respiratory impairment (FEV1 percent reference: mild, moderate, and ≤ moderately severe). We assessed predictors of prevalence (age, mining tenure, and geography) using logistic regression, and compared respiratory outcomes among similar-aged miners (49–60 years) who had worked only since the 1970 dust rule (post-1970; n = 3, 586) to those who worked before and since 1970 (pre/post-1970; n = 4, 434). Results: Among FBLP claimants, 8.5% had advanced CWP or PMF with the highest rates among younger (<56 years: 10.8%) and older (>70 years: 8.3%) miners. 20.6% of claimants had ≤ moderately severe impairment, enough to be considered disabling for mining work (FEV1 < 60% ref). Rates of advanced CWP and PMF were significantly higher among post-1970 compared with pre/post-1970 miners (5.7% vs. 3.8%, p < 0.0001; 7.1% vs. 3.8%, p < 0.0001, respectively), while the percent of miners with disabling impairment was similar between the groups (16.7% vs. 17.6%, p = 0.9190). Conclusions: We found high rates of pulmonary impairment and advanced radiologic pneumoconiosis in former coal miners applying for FBLP benefits. The prevalence of advanced pneumoconiosis was significantly higher in miners who only worked after 1970, suggesting that dust control regulations were ineffective in preventing severe disease.